Engineering Solar Cell Absorbers by Exploring the Band Alignment and Defect Disparity: The Case of Cu‐ and Ag‐Based Kesterite Compounds. (19th October 2015) - Yuan, Zhen‐Kun; Chen, Shiyou; Xiang, Hongjun; Gong, Xin‐Gao; Walsh, Aron; Park, Ji‐Sang; Repins, Ingrid; Wei, Su‐Huai
Abstract : The development of kesterite Cu2 ZnSn(S, Se)4 thin‐film solar cells is currently hindered by the large deficit of open‐circuit voltage ( V oc ), which results from the easy formation of CuZn antisite acceptor defects. Suppressing the formation of CuZn defects, especially near the absorber/buffer interface, is thus critical for the further improvement of kesterite solar cells. In this paper, it is shown that there is a large disparity between the defects in Cu‐ and Ag‐based kesterite semiconductors, i.e., the CuZn or CuCd acceptor defects have high concentration and are the dominant defects in Cu2 ZnSn(S, Se)4 or Cu2 CdSnS4, but the AgZn acceptor has only a low concentration and the dominant defects are donors in Ag2 ZnSnS4 . Therefore, the Cu‐based kesterites always show p‐type conductivity, while the Ag‐based kesterites show either intrinsic or weak n‐type conductivity. Based on this defect disparity and calculated band alignment, it is proposed that the V oc limit of the kesterite solar cells can be overcome by alloying Cu2 ZnSn(S, Se)4 with Ag2 ZnSn(S, Se)4, and the composition‐graded (Cu, Ag)2 ZnSn(S, Se)4 alloys should be ideal light‐absorber materials for achieving higher efficiency kesterite solar cells. Abstract : A new strategy is proposed to overcome the V oc bottleneck and increase the efficiency of the kesterite solar cells. This is achieved by forming composition‐graded (Cu1– x Ag x )2 ZnSn(S, Se)4 alloys as the absorber layer.